(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The study was conducted in the coastal homesteads of Bangladesh to assess the growth and development of Bambusa vulgaris Schrad. ex Wendl. planted in 2010 and 2011 using branch cutting seedlings. Trials were established at 5 different sites of the coastal belt. Data on seedling survival, culm height, culm diameter, culms production etc. were recorded from 4.0 years old and 3.0 years old two trial plantations. The result revealed that significantly greater culm height was 16.30 m, culm diameter was 5.29 cm from Rangabali site but greater number of culms/clump was 21.20 at Char Kukri-Mukri site at the age of 4.0 years raised in 2010. In the plantations of 2011, the significantly greater height was 13.21, greater diameter was 4.55 cm and greater number of culms/clump was 15.44 from Rangabali site at the age of 3.0 years. The promising culm height was recorded from Rangabali and Char Kukri-Mukri sites and it was grown up to 20.53 m and 17.94 m respectively of 4 years old plantations. Therefore, large scale plantations with B. vulgaris in the coastal homesteads can be established for the development of bamboo vegetation in the remote coastal areas of Bangladesh. Thus, homesteads bamboo plantations can provide income-generating opportunities for poor farmers and can protect habitation and properties of the coastal population from natural disaster as safeguard. Asiat. Soc. Bangladesh, Sci. 41(2): 123-131, December 2015